Religious, environmental, and political factors affecting the acceptance of nuclear power plants - Lee, Ye Ji; Kim, Wan-Yong (International Journal of Management and Sustainability, 2024)
This study investigated the role of religious factors as determinants of public acceptance of nuclear power plants. Mixed views have been expressed regarding nuclear power plants, depending on whether the benefits of nuclear energy, such as economic benefits and convenience, are weighed against potential risks or vice versa. Various factors are assumed to influence views on nuclear power. Using financial panel survey data, the findings revealed that the presence of religious belief alone did not significantly impact acceptance of nuclear power plants. Nonetheless, the Catholic group exhibited a lower level of acceptance of nuclear power plants. In addition, the difference between the Buddhist and Protestant groups is not statistically significant because both religions have not established a clear view of nuclear energy. By analyzing religious factors as determinants of nuclear power acceptance in addition to environmental and political factors, this study provides evidence that individual religion or type of religion has a significant influence on nuclear power policy.